GAMBARAN STATUS GIZI ANAK BARU MASUK SEKOLAH DASAR DAN PRESTASI BELAJAR SISWA DI KECAMATAN MEDAN SELAYANG TAHUN AJARAN 2016/2017 - Ruth Apriyanti; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The attainment of human resources quality and competitivenesscan be achieved in a healthy society. Primary school age student are the future generation who can bring change to the nation. The new primary student requires an adjustment to school environment and food other than at home. The purpose of this study is to describe the prevalence of nutritional status thenew primary studentand student learning achievement in sub-district of Medan Selayang academic year 2016/2017. This research was a descriptive survey with cross-sectional design. The population was all new primary studentin sub-district of Medan Selayang academic year 2016/2017. The minimum sample as many as 128 students. Selected school were public elementary schools 066656 and 065011. The sampling method using a multi-stage randomsampling. The results showed that the new primary studentschool at 066656 students who have a Body Mass Index(BMI) by Age category of very underweight and less learning achievement there is 28.6%, the normal category and less learning achievement there is 19.4%. Most students at 066656 who have a BMI by Age category of underweight and adequate learning achievement 71.4%. At school 065011 merely on students with BMI by Age normal categories that have less learning achievement there is 6.7%. Students with BMI by Age, very underweight with adequate learn achievement 75%, and excellent 25%. The nutritional status ofHeight by Agethe new primary studentat 066656 students who have Height by Age categories severe stunting and high who has adequate learning achievement 100%. Students with Height by Age categorized stunting and less learning achievement respectively 50%. Students withHeight by Age at 065011 category of severe stunting and adequately learning achievement 100%. Stunting category and who has less learning achievement 8.3%, adequate 83,3%, and excellent 8.3%. The study descriptive in order that a healthy society, then every elementary school helped to control the role of community health centers new primary studentthrough the surveillance and the weighing and high school children to perform anthropometric measurements and do counseling through the school health. Keywords: New Primary Student, Nutritional Status, Learning Achievement